Retaining Employees through Organizational Social Climate, Sense of Belonging and Workplace Friendship: A Research in the Financial Sector - Elif Bilginoğlu; Uğur Yozgat (Istanbul Business Research)
This paper examined the impact of organizational social climate on employees’ sense of belonging, its impact on employees’ intention to leave as well as the moderating effect of workplace friendships on this relationship. Using a convenient sampling method on financial sector employees working in Istanbul, Turkey, a survey was conducted. A total of 403 employees were surveyed. The findings of this study revealed that organizational social climate is positively associated with sense of belonging, while organizational social climate, sense of belonging and workplace friendship are negatively associated with intention to leave the organization. According to the findings, the workplace friendship moderates the relationship between sense of belonging and intention to leave. This paper demonstrated that social interactions in the workplace play a vitally important role in employees’ intentions to leave the organization. This contributes to conceptual understanding of the job embeddedness theory, which suggests that the relationships are one of the key factors that keep individuals in organizations. This paper highlighted the potential for employee turnover to directly / indirectly arise from the employees’ sense of belonging, social climate and workplace friendships acquired in the organization.